ANALISIS KUALITAS APLIKASI SI JEMPOL MENGGUNAKAN METODE USABILTY TESTING DI JASDAM II SRIWIJAYA - Ayu, Niken; Supratman, Edi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The rapid development of information technology has encouraged military organizations, including Jasdam II Sriwijaya, to adopt digital applications in order improve administrative efficiency and service quality. One of the innovations implemented is the SI Jempol application, which is designed to facilitate personnel administr ative services. This study aims to analyze the quality of the SI Jempol application using the usability testing method to evaluate its ease of use, effectiveness, and user satisfaction. Data were collected through a questionnaire based on the System Usability Scale (SUS), distributed to a group of application users. The analysis was carried out by calculating the SUS score and identifying both the strengths and weaknesses of the application. The findings indicate that SI Jempol achieved an average usability score categorized as [e.g., “good” or “fairly satisfactory” – to be adjusted according to results], suggesting that the application is effective and acceptable to users. However, several aspects still require improvement, such as. In conclusion, the SI Jempol application has strong potential to be further developed as a digital service that supports administrative performance within Jasdam II Sriwijaya.